Should genetic testing become a standard component of clinical trials in order to advance evidence-based cardiology practice? - Watkins, H (2004)
Medical therapy currently assumes that all individuals with a given condition should be treated in the same way, guided by empirical evidence from clinical trials. This ignores interindividual differences, which may predict variable therapeutic efficacy or adverse drug reactions. Considerable evidence suggests that genetic makeup determines much of this variability, and major efforts are being made to harness genetics to predict drug responses. Pharmacogenetics can improve the power and informativeness of clinical trials and increase the value of new or existing drugs. However, the precise characteristics of the underlying genetic variants will strongly impact the ease with which pharmacogenetic studies can deliver these high expectations, to the extent that it is no yet efficient to systematically include genetic testing in clinical trials.